2016
DOI: 10.5194/tc-10-585-2016
|View full text |Cite
|
Sign up to set email alerts
|

Error assessment of satellite-derived lead fraction in the Arctic

Abstract: Abstract. Leads within consolidated sea ice control heat exchange between the ocean and the atmosphere during winter, thus constituting an important climate parameter. These narrow elongated features occur when sea ice is fracturing under the action of wind and currents, reducing the local mechanical strength of the ice cover, which in turn impact the sea ice drift pattern. This creates a high demand for a highquality lead fraction (LF) data set for sea ice model evaluation, initialization, and for the assimil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…The mean differences over FYI are within 3-5 cm, while locally these can be more than 10 cm. Since the lead fraction in the areas of seasonal ice is higher than over thick MYI (Willmes and Heinemann, 2016;Ivanova et al, 2016;Röhrs et al, 2012;Bröhan and Kaleschke, 2014), one can expect that the observed difference in freeboard estimates does not come from the same causes mentioned above for MYI areas. The positive differences most likely reflect the underestimation of freeboard retrieved by the TP method as was found by Kwok et al (2007) from comparison with the freeboards adjacent to leads detected on satellite images and collocated with ICESat data.…”
Section: The Original Algorithm Used In the Tp Methodsmentioning
confidence: 94%
“…The mean differences over FYI are within 3-5 cm, while locally these can be more than 10 cm. Since the lead fraction in the areas of seasonal ice is higher than over thick MYI (Willmes and Heinemann, 2016;Ivanova et al, 2016;Röhrs et al, 2012;Bröhan and Kaleschke, 2014), one can expect that the observed difference in freeboard estimates does not come from the same causes mentioned above for MYI areas. The positive differences most likely reflect the underestimation of freeboard retrieved by the TP method as was found by Kwok et al (2007) from comparison with the freeboards adjacent to leads detected on satellite images and collocated with ICESat data.…”
Section: The Original Algorithm Used In the Tp Methodsmentioning
confidence: 94%
“…Synthetic Aperture Radar (SAR) or microwave imagery can be used to obtain sea ice surface details with minimum cloud influence. Kwok (1998) used the RADARSAT Geophysical Processor System (RGPS) to estimate the deformation of sea ice and identify the linear kinematics features, i.e., sea ice leads. Röhrs and Kaleschke (2012) presented an algorithm applied to the passive microwave imagery from the Advanced Microwave Scanning Radiometer for EOS (AMSR-E) to detect sea ice leads wider than 3 km.…”
Section: Methodsmentioning
confidence: 99%
“…One reason is a lack of observations of sea ice leads with sufficient spatial and temporal coverage. This hampers our understanding of the variability of sea ice leads in the Arctic Ocean, and their relationship with Arctic sea ice cover (Ivanova et al, 2016;Wernecke and Kaleschke, 2015). Another reason is that sea ice leads constitute an unrepresented process in numerical prediction systems and climate models due to their highly nonlinear, small-scale and intermittent characteristics (Spreen et al, 2017;Wang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The lack of existing modeling capacity has meant that our understanding of linear kinematics of sea ice is mainly based on buoys and satellite observations of ice drift [e.g., Kwok et al , ; Lindsay , ; Weiss and Marsan , ; Marsan et al , ; Rampal et al , ; Stern and Lindsay , ; Hutchings et al , ; Herman and Glowacki , ] and satellite as well as airborne measurements for sea ice leads [ Fily and Rothrock , ; Stone and Key , ; Lindsay and Rothrock , ; Miles and Roger , ; Tschudi et al , ; Onana et al , ; Broehan and Kaleschke , ; Willmes and Heinemann , , ]. Here we exploit the fact that lead area fraction data sets for the last decade have become available [ Roehrs and Kaleschke , ; Wernecke and Kaleschke , ; Willmes and Heinemann , , ; Ivanova et al , ], which can be used to evaluate sea ice models.…”
Section: Introductionmentioning
confidence: 99%